2018
DOI: 10.26804/ager.2018.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy, and economic analysis of a geothermal power plant

Abstract: Citation:Kazemi, H., Ehyaei, M.A. Energy, exergy, and economic analysis of a geothermal power plant. Advances in Geo-Energy Research, 2018, 2(2): 190-209, doi: 10.26804/ager.2018.07.Corresponding author: *E-mail: aliehyaei@yahoo.com Keywords:Geothermal cycle Organic Rankine Cycle exergy Abstract:The current study aimed at designing a geothermal power plant in the Nonal area in Damavand district for simultaneous generation of thermal energy the electric power in the network of Damavand City and a part of Tehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…[ 31 ] For the operating and maintenance cost, 3% of the initial cost is considered. And, it can be calculated by the following equation [ 30,32 ] O M = N = 1 20 0.04 × total cost false( 1 + 0.08 false) N where OM is the operating and maintenance cost. Total cost represents the total investment costs.…”
Section: Modelingmentioning
confidence: 99%
“…[ 31 ] For the operating and maintenance cost, 3% of the initial cost is considered. And, it can be calculated by the following equation [ 30,32 ] O M = N = 1 20 0.04 × total cost false( 1 + 0.08 false) N where OM is the operating and maintenance cost. Total cost represents the total investment costs.…”
Section: Modelingmentioning
confidence: 99%
“…As the world's largest energy producer and consumer, China is developing clean, carbon-free and efficient new energy sources to achieve the goal of carbon neutralization and promote a harmonious relationship between humans and nature. Geothermal energy is one of the most important renewable energy resources because of its great exploitation potential and abundant reserves (Kazemi and Ehyaei, 2018;Chen et al, 2019). Therefore, paying attention to the rational development and utilization of geothermal resources is of great significance to realize the energy revolution.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in recent years on energy, exergy, economic and environmental analyses, and optimization of various power generation systems, including combined heat and power, renewable energy, and other plants [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%